COPS-SLS usage for dynamic policy-based QoS management over heterogeneous IP networks. - Thi Mai Trang Nguyen
While each IP domain can deploy its own strategy to manage network resources, multimedia traffic needs end-to-end QoS management to obtain an overall service level. The provision of end-to-end QoS over a heterogeneous environment implies the negotiation of a mutually acceptable SLA. This article presents the use of the COPS-SLS protocol as a generic protocol for automatic service-level negotiation and the integration of this protocol in an overall QoS management architecture to manage service levels over multiple domains deploying different QoS technologies.
Keywords: COPS-SLS protocol; SLA; Automatic service-level negotiation; Dynamic policy-based management; End-to-end QoS management; Heterogeneous IP networks; Management architecture; Multimedia traffic; Network resources; Protocol integration